Deep Brain Stimulation of Heschl Gyrus: Implantation Technique, Intraoperative Localization, and Effects of Stimulation. Issue 6 (14th August 2015) - Donovan, Chris; Sweet, Jennifer; Eccher, Matthew; Megerian, Cliff; Semaan, Maroun; Murray, Gail; Miller, Jonathan
Abstract : BACKGROUND: Tinnitus is a source of considerable morbidity, and neuromodulation has been shown to be a potential treatment option. However, the location of the primary auditory cortex within Heschl gyrus in the temporal operculum presents challenges for targeting and electrode implantation. OBJECTIVE: To determine whether anatomic targeting with intraoperative verification using evoked potentials can be used to implant electrodes directly into the Heschl gyrus (HG). METHODS: Nine patients undergoing stereo-electroencephalogram evaluation for epilepsy were enrolled. HG was directly targeted on volumetric magnetic resonance imaging, and framed stereotaxy was used to implant an electrode parallel to the axis of the gyrus by using an oblique anterolateral-posteromedial trajectory. Intraoperative evoked potentials from auditory stimuli were recorded from multiple electrode contacts. Postoperatively, stimulation of each electrode was performed and participants were asked to describe the percept. Audiometric analysis was performed for 2 participants during subthreshold stimulation. RESULTS: Sounds presented to the contralateral and ipsilateral ears produced evoked potentials in HG electrodes in all participants intraoperatively. Stimulation produced a reproducible sensation of sound in all participants with perceived volume proportional to amplitude. Four participants reported distinct sounds when different electrodes were stimulated, with more medial contacts producing tones perceived as higher in pitch. Stimulation was not associated with adverse audiometric effects. There were no complications of electrode implantation. CONCLUSION: Direct anatomic targeting with physiological verification can be used to implant electrodes directly into primary auditory cortex. If deep brain stimulation proves effective for intractable tinnitus, this technique may be useful to assist with electrode implantation.